PENGARUH PENAMBAHAN IMPELLER PADA FASE AEROBIK TERHADAP EFISIENSI KINERJA SEQUENCING BATCH REACTOR PADA LIMBAH CAIR INDUSTRI TAHU - Irma Ilham Yadaturrahmah; Novirina Hendrasarie (Envirotek : Jurnal Ilmiah Teknik Lingkungan, 2021)
Currently the tofu industry is growing. The waste produced from the tofu industry will be a problem for the environment. Tofu industrial wastewater treatment can be done by biological treatment because it can reduce the organic content in tofu wastewater. One of the effective and efficient waste treatments is Sequencing Batch Reactor (SBR). The principle of operation of the SBR is fill and draw, which consists of five stages, fill,, reaction, settle, decand and idle.. SBR is operated with a hydraulic retention time (HRT) and varying stirring speeds, namely 24, 36 and 48 hours respectively and stirring speeds of 50, 100 and 150 rpm. The results showed that the optimal HRT and stirring speed were 48 hours and 150 rpm, respectively. With the efficiency of BOD, PO4 and Total N removal produced, respectively 93,33%, 90,97% and 93,73%.